The Effect of Guided Imagery Techniques on Elderly Blood Pressure Hypertension in South Purwokerto - Utami, Mega Putri; Siwi, Adiratna Sekar; Khasanah, Suci (Journal of Bionursing, 2024)
Background: Hypertension has become a leading cause of death globally, often referred to as "The Silent Killer." The therapeutic management of hypertension includes both pharmacological and non-pharmacological approaches, one of which is guided imagery relaxation. Objective: To assess the influence of guided imagery relaxation techniques on blood pressure in elderly individuals with hypertension in South Purwokerto. Method: This study utilizes a quasi-experimental design with a pretest-posttest control group, employing purposive sampling to obtain 30 control and 30 intervention groups of elderly individuals with hypertension. The intervention includes guided imagery techniques via video and audio guides for 10-15 minutes before sleep over one week. Measurements are taken before and after the intervention from days one to six. Statistical analyses involve the Paired T-Test, Mann Whitney U, and Wilcoxon Signed Rank tests. Results: The analysis of blood pressure using the Mann-Whitney U test shows a p-value of 0.000 for systolic pressure and 0.014 for diastolic pressure. The Paired T-test results indicate a p-value of 0.000 for systolic intervention and 0.021 for diastolic control. The Wilcoxon Signed Rank test results show a p-value of 0.393 for systolic control and 0.000 for diastolic intervention. Conclusion: Guided imagery significantly lowers both systolic and diastolic blood pressure in the intervention group compared to the control group (p-value < 0.05). It is recommended as an effective therapy for hypertension in the elderly, underscoring the need for meticulous nursing care documentation.